Animal protection in Spain: Historical evolution and consequences of the entry into force of Law 2/2023, of March 13, on the Protection, Welfare, and Keeping of Companion Animals and other animal welfare measures - Cantero Berlanga, Manuel Damián; Mendez Rocasolano, Maria; Valencia Virosta, Alejandro (Revista de Derecho Ambiental, 2024)
In recent years, the mistreatment of animals has increased notably, which has motivated the legislators to regulate this social problem in a different way than in the past. This research aims to expose the Spanish regulatory tradition regarding these acts of cruelty, which has allowed the establishment of a pioneering law that allows the effective protection of animals against their aggressors. Throughout the article, the reader will be able to observe the different theories that the legislator has been following and how they have been positivized in the Spanish legal system. Finally, this research aims to specify the protected legal right on which the different rules are based and, at the same time, a study of the criminal type and its continuous modifications up to the present time. It is important to highlight, and this has been the intention of this research, the importance of recent of this research, the importance of the recent regulation in the Spanish legal system, which has Spanish legal system and that it has served as an example for other countries where animal rights have not yet been animal rights have not yet been treated in a remarkable way, leaving these living beings unprotected these living beings unprotected against the barbarity and uncivil behaviors of human beings. Uncivil behaviors of human beings when our responsibility should be to watch over and protect the world we live in.